Knowledge, perceived need for education, and willingness to participate in bioterrorism preparedness among students in an indian dental institute: A questionnaire study - Sumeet Bhatt; Gururaghavendran Rajesh; Deepika Thakur (Medical Journal of Dr. D.Y. Patil University, 2017)
Objectives: An act of bioterrorism may compromise the local medical system and require whole of the healthcare workforce. The purpose of the present study was to assess the knowledge, perceived need for education, and willingness to participate in bioterrorism management among students in an Indian dental institute. Materials and Methods: A total of 231 dental students, including undergraduates and postgraduates, participated in this study conducted in the year 2014. Dental students' knowledge, perceived need, and willingness were assessed using a self-administered questionnaire. Results: More than 90% of both undergraduate and postgraduate students were willing to provide care during a bioterrorism attack. The actual knowledge was observed to be very low in both groups. Perceived knowledge as well as actual knowledge was statistically higher in the postgraduate group (P < 0.05). Most of the participants were of the opinion that they need more education regarding bioterrorism and that it should be added to dental curriculum. The majority of the participants showed willingness to attend continuing education programs on bioterrorism. Conclusions: The dental students demonstrated low knowledge but high willingness to provide care. A policy-driven approach to include bioterrorism management in dental education and organization of more continuing education programs is recommended to improve knowledge and develop necessary skills. This will help develop a workforce efficient in providing care during a possible act of bioterrorism.